ANALYSIS OF THE WORK SYSTEM OF CONTRACT PARAMEDICS AND CIVIL SERVANTS IN GAYO LUES RSUD IN TERMS OF IJARAH BI AL-'AMAL CONTRACT - Juni Sakinah (JURISTA: Jurnal Hukum dan Keadilan, 2018)
Providing good health service is the main priority that must be met by paramedics. It’s a form of responsibility for the work they are carrying out based on the contractual agreement they have agreed with the health institution in questian. in Islamic law, the contract of cooperation between paramedics and the relevant health care institution is a form of contractual agreement using the concept of the ijarah contract bi al-amal. The purpose of this study is to find out the work system of contract paramedics and civil servants in Gayo Lues Hospital as well as review of the ijarah bi al-‘amal contract towards the work system applied to contract paramedics and civil servants in the Gayo Lues Hospital. The type of research used in this study is a type of qualitative research that is descriptive analysis, which is a method that aims to draw a systematic, factual and accurate description of the facts, the nature and the relationship between the phenomena to be known. Data collection techniques in this study were carried out by observation, interview, and documentation data. The results of the study show that the work system implemented by the hospital management for paramedics does not result in disputes between one another. In the perspective of Islamic law, the work system applied by the hospital management to paramedics is in accordance with the theory of ijarah contract bi al-'amal and its implementation is in accordance with the pillars of the ijarah contract, which consists of 'aqid (tenants and leasing parties), ma 'qud'alaih (object of agreement or rent reward), benefits and sighat (ijab and qabul). However, in the payroll system there are differences between contract paramedics and civil servants, PNS paramedics the right to receiving salary is more certain than contract paramedics, this is contrary to the hadith of the Prophet who ordered to hasten payment of wages for workers.